Welcoming Confusion, Embracing Uncertainty: Educating Teacher Candidates in an Age of Certitude - Gordon, Mordechai (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2006)
This essay challenges the current emphasis on certainty, measurement and control in the field of education and the widespread view that confusion hurts students. Drawing on some recent analyses of Socrates as well as my own interpretation of his dialogues, I discuss how he might respond to the quest for certainty in education. Socrates would want us to welcome confusion and embrace uncertainty, and urge us to reconceptualize the quest for certainty as an ongoing process aimed at increasing complexity and enhancing understanding. Based on the insights I gleaned from Socrates, I argue that creating a space for perplexity and uncertainty in our classrooms is crucial for the goal of fostering citizens who are critical and independent thinkers. I conclude this essay by proposing a number of ways in which teacher educators can help their students welcome confusion and embrace uncertainty.